Prototipe Media Pembelajaran Bahasa Indonesia Berbasis Komik Audio Visual Bermuatan Nilai Antikorupsi untuk Siswa SMA - Wulan, Andi Naga; Subyantoro, Subyantoro; Wagiran, Wagiran (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Technology-based learning media is a means of providing students with an understanding of the subject matter as well as internalizing character values. This research aims to describe the creation of a prototype for audio-visual comic media containing anti-corruption values as Indonesian language learning material. This audio visual comic media was created with the help of artificial technology (AI). This research was carried out by literature study. The findings show that the development of audio-visual comic media is still stagnant, even though this media has great potential in improving the quality of learning. Apart from that, there are not many learning media that contain anti-corruption character values in Indonesia. Therefore, audio-visual comic media containing anti-corruption values will provide great contributions and benefits in creating an educated and characterful generation.